2020
DOI: 10.3389/fonc.2020.00145
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Ancestry in 1,002 Brazilian Colorectal Cancer Patients From Barretos Cancer Hospital

Abstract: Background: Colorectal cancer (CRC) is the third most frequent and the second deadliest cancer worldwide. The ethnic structure of the population has been gaining prominence as a cancer player. The purpose of this study was to determine the genetic ancestry of Brazilian CRC patients. Moreover, we intended to interrogate its impact on patients' clinicopathological features.Methods: Retrospective observational cohort study with 1,002 patients with CRC admitted from 2000 to 2014 at Barretos Cancer Hospital. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 58 publications
2
22
0
3
Order By: Relevance
“…Previous studies have reported that polyps and colorectal cancer are more frequent among African Americans than non-Hispanic Whites [ 64 66 ]. In the present study, as expected [ 30 , 67 , 68 ], we observed a high heterogeneity of the ancestry proportions in our study population, yet, we did not find any difference between genetic ancestry and the groups of precursor lesions evaluated. This result could be due to the small number of cases within each group analyzed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have reported that polyps and colorectal cancer are more frequent among African Americans than non-Hispanic Whites [ 64 66 ]. In the present study, as expected [ 30 , 67 , 68 ], we observed a high heterogeneity of the ancestry proportions in our study population, yet, we did not find any difference between genetic ancestry and the groups of precursor lesions evaluated. This result could be due to the small number of cases within each group analyzed.…”
Section: Discussionsupporting
confidence: 82%
“…The genetic ancestry of 81 patients with colorectal precursor lesions with available blood was determined by 46 autosomal ancestry informative markers (AIMs), which consist of insertion-deletion polymorphisms (INDELs) as described [ 30 ]. A multiplex PCR was followed by a fragment analysis performed by ABI 3500xL Genetic Analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several studies were conducted on this patient population to determine their genetic-based ethnicity and correlate their ethnicity with clinical characteristics. These studies observed considerable admixture in the genetic composition 35 38 .…”
Section: Methodsmentioning
confidence: 96%
“…In addition, several studies were conducted on this patient population to determine their genetic-based ethnicity and correlate their ancestry with clinical characteristics. These studies observed considerable admixture in the genetic composition [35][36][37][38] .…”
Section: Patient Eligibility Biospecimen and Clinical Datamentioning
confidence: 96%